Analisis Kesiapan Keamanan Area Staff Security Check Point (SSCP) di Bandar Udara Adi Soemarmo - Boyolali - Juliansyah, Dio Dzaky; Wahyudono, Wahyudono; Adriansyah, Feri (Sekolah Tinggi Teknologi Kedirgantaraan, 2025)
This study analyzes the readiness of the Staff Security Check Point (SSCP) at Adi Soemarmo Airport – Boyolali in ensuring aviation security. Using a descriptive qualitative method with a gap analysis approach, the research compares the actual conditions with regulatory standards regarding facility readiness, personnel availability, and SOP implementation. Data were collected through observation, interviews, and documentation during On the Job Training (OJT). The findings reveal several discrepancies, including inadequate lighting, lack of signboards, absence of X-ray equipment, insufficient personnel, and suboptimal SOP enforcement. These issues hinder the effectiveness of the current security operations. The study proposes short-term improvements such as lighting and signage enhancements, and long-term solutions including reactivation of the main SSCP and personnel additions. Stronger supervision is also recommended to ensure SOP compliance. These measures aim to align SSCP operations with national aviation security standards and minimize unlawful interference risks.